Functional Results Evaluation of Primary Surgical Repair of Unilateral Cleft Lip by Tennison Technique According To Electromyographic Data (Journal of Hama University, 2020)
The research aims to evaluate the results of Tennison technique in the normal anatomical repositioning of the muscles involved in the cleft and thus the functional aspect. The study sample included children aged 2.5 - 4 years who had a full unilateral cleft lip  who underwent a three-month primary surgical lip repair with Tennison technique. According to the admission and exclusion criteria, the main sample of the study consisted of (20) patients, which was divided into two groups: a group of cleft lip patients included (10) children aged 2.5-4 years who had a full unilateral cleft lip who underwent a primary surgical repair of the lip at the age of three months with Tennison technique, the control group consisted of (10) healthy children aged 2.5 - 4 years. The EMG test was performed for both the Orbicular Muscle of Mouth, Elevator muscle of Upper Lip and Wing of Nose of both groups with intramascular EMG technique using the ENMG device located at the neurological clinic at Tishreen University Hospital.The result showed no significant statistical difference in muscle activity values for Elevator muscle of Upper Lip and Wing of Nose in both cleft and noncleft side for a group of cleft patients, as well as no significant statistical difference in muscle activity values for Orbicular Muscle of Mouth between study group and control group, Consequently, we conclude that Tennison technique restores the closest anatomical positioning to muscle fibers of studied muscles.